Pelatihan online internet sehat sebagai media pembelajaran bagi siswa-siswi SMK Nurul Huda Pemulutan Barat - Rasmila Rasmila; Rahayu Amalia; Jemakmun Jemakmun; Aan Restu Mukti (Universitas Hamzanwadi, 2021)
Internet or interconnection in the digital era is closely related to everyday life from children to adults as an assistive medium in carrying out and connecting various human activities effectively, accurately, and efficiently. The internet is also a communication network that connects one electronic media with other electronic media quickly and precisely. Moreover, at this time, we are currently hit by the COVID 19 pandemic. Online learning is a regulation issued by the Government as a preventive measure against COVID 19, and the quality of online learning media can influence its effectiveness. This community service aims to educate 20's students of SMK Nurul Huda Pemulutan Barat about the healthy internet as a learning medium in their daily lives. The result has shown that the students know about Healthy Internet